Understanding The Spread of Evidence-Informed Decision Making in a Government Health Department in Canada - Workentine, Stephanie (My University, 2014)
Background. In order to deliver effective and efficient public health services, the best available research evidence should be considered when making public health decisions. The process of evidence-informed decision making (EIDM) involves searching for research evidence, appraising and synthesizing the high quality evidence, and adapting the evidence with consideration of local contextual factors and community preferences. For many public health departments achieving EIDM has been a challenge. Methods. This study aimed to learn how EIDM spread through interpersonal interactions within the health department of a provincial government in Canada. The health department was selected based on anecdotal evidence suggesting that ideas of EIDM had diffused within this department. Employees were invited to participate in an electronic survey about their interactions regarding EIDM. The data collected from this survey were analyzed using social network analysis methods. This helped to show how the interpersonal connections helped to spread the ideas of EIDM within the organization. Results. In this organization EIDM discussion occurred most often within the organizational divisions, whereas influence for EIDM often occurred both within and between divisions. The type of relationship that appeared most important in discussion of EIDM was colleague relationships, while supervisors were more important for encouraging use of EIDM. Furthermore, individuals in leadership positions within the organization were shown to have played an important role in the diffusion of EIDM. Limitations and Conclusions. Low participation resulted in a limited picture of the whole network of this organization. The use of social network analysis is a relatively novel approach for studying the diffusion of EIDM, and there are challenges to this approach that requires special consideration when working with organizations.
Keywords: Knowledge Translation; Social Network Analysis; Evidence-informed decision making; Diffusion of Innovations